Financing of Innovative Activity in Service Field Enterprises (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Innovative development in the service sector plays an important role in increasing the competitiveness of companies in a rapidly changing business environment. This article discusses the importance of constantly monitoring changes and adapting strategy to new challenges and opportunities. Key factors that underline the need for this approach are discussed, such as the dynamic market, customer needs, competitive environment, and technological advances. The authors say that constant monitoring and adaptation of strategy helps companies to be agile, innovative and competitive, and ensures successful development in the long term.